La diferencia entre amor y deseo: un certamen poético barcelonés de 1584 - Helena Rovira (Moderna Språk)
Ms. B2470 of the Hispanic Society of America transmits a poetry contest held in Barcelona at the end of 1584, whose 34 compositions are all focused on a single theme: the difference between love and desire. The choice of a profane subject is a singular element, because most of the contests of the late sixteenth century are religious. It is a practically unknown contest containing poems mainly written in Spanish, but also some in Catalan, one in Latin and one in Italian. Among the participants, there are outstanding figures as Francesc Calça, Esteve de Corbera, Dionís Jeroni Jorba and four members of the family March of Montcortès, but there are also several poets hitherto unknown. Another remarkable aspect is an elegy on the death of the Valencian poet Gaspar Gil Polo inserted in the text, just before the judgment. This elegy brings new light on the date of death of the Diana enamorada’s author, who had to die before December 31, 1584. It also makes us consider the possibility that the author of the sonnet presented to this contest was not him but his son, also called Gaspar Gil Polo.